Identification and characterisation of mitochondrial sequences integrated into the ovine nuclear genome. (31st May 2021) - Féménia, M.; Charles, M.; Boulling, A.; Rocha, D.
Summary: Mitochondrial DNA sequences are frequently transferred into the nuclear genome, generating nuclear mitochondrial DNA sequences (NUMTs). Here, we analysed, for the first time, NUMTs in the ovine genome. We obtained 760 alignment matches covering 513.8 kbp of the sheep nuclear genome. After a merging step, we identified 390 NUMT regions with a total length of ~720 kbp, representing 0.02% of the nuclear genome. We discovered copies of all mitochondrial regions and found that most NUMT regions are intergenic or intronic. Ovine NUMTs are mostly not transcribed. However, we identified within some of the NUMTs, potential new genes encoding nuclear humanin isoforms. To rule out the possibility that the identified NUMTs could be artifacts of the Oar Rambouillet v1.0 genome assembly, we validated experimentally nine NUMT regions by PCR amplification. As we found several NUMT regions showing high similarity to the mitochondrial genome that potentially could pose a risk to ovine DNA mitochondrial studies, special care must be taken for the selection of primers for PCR amplification of mitochondrial DNA sequences.